The creation of autotetraploid provides insights into critical features of DNA methylome changes after genome doubling in water spinach (Ipomoea aquatica Forsk) - Hao, Yuanyuan; Su, Xiao; Li, Wen; Li, Lin; Zhang, Yu; Mumtaz, Muhammad Ali; Shu, Huangying; Cheng, Shanhan; Zhu, Guopeng; Wang, Zhiwei (Frontiers in Plant Science, 2023)
Water spinach (Ipomoea aquatica Forsk) is an essential green leafy vegetable in Asia. Autotetraploid water spinach was created for the first time. Compared with the diploid parent, autotetraploid water spinach had wider leaves, thicker petioles and stems, thicker and shorter adventitious roots, longer stomas, and larger parenchyma cells. Furthermore, DNA methylation and transcriptome of tetraploid and diploid were compared using Whole Genome Bisulfite Sequencing (WGBS) and RNA-sequencing techniques. The whole genome methylation level of the autotetraploid was slightly higher than that of the diploid. Compared with the diploid, 12281 Differentially Methylated Regions (DMRs)were found in the autotetraploid, including 2356 hypermethylated and 1310 hypomethylated genes, mainly enriched in 'Arginine and Proline metabolism', 'beta − Alanine metabolism', 'Plant homone signal translation', 'Ribome', and 'Plant − pathgen interaction' pathways. Correlation analysis of transcriptome and DNA methylation data showed that 121 differentially expressed genes undergone differential methylation, related to four pathways 'Other types of O-glycan biosynthesis', 'Terpenoid backbone biosynthesis', 'Biosynthesis of secondary metabolites', and 'Metabolic paths'. This work obtained important autotetraploid resources of water spinach and revealed the genomic DNA methylation changes after genome doubling, being helpful for further studying the molecular mechanism of variations caused by polyploids of the Ipomoea genus.